Servant Leadership: A Review and Synthesis - van Dierendonck, Dirk (Journal of Management, 2011)
Servant leadership is positioned as a new field of research for leadership scholars. This review deals with the historical background of servant leadership, its key characteristics, the available measurement tools, and the results of relevant studies that have been conducted so far. An overall conceptual model of servant leadership is presented. It is argued that leaders who combine their motivation to lead with a need to serve display servant leadership. Personal characteristics and culture are positioned alongside the motivational dimension. Servant leadership is demonstrated by empowering and developing people; by expressing humility, authenticity, interpersonal acceptance, and stewardship; and by providing direction. A high-quality dyadic relationship, trust, and fairness are expected to be the most important mediating processes to encourage self-actualization, positive job attitudes, performance, and a stronger organizational focus on sustainability and corporate social responsibility.